Nominalismus als universitäre Spekulationskontrolle - Hoenen, Maarten J. F. M. (Recherches de théologie et philosophie médiévales, 2006)
This article provides a historico-philosophical profile of late-medieval nominalism. It shows how nominalism placed limitations on the use of logic and natural reason in academic theology. In the first part, the historical meaning and use of the notions ‘moderni’ and ‘nominales’ are explored. In the second part, the methodology of the ‘moderni’ and ‘nominales’ is investigated, showing how nominalist understanding of logic and natural reason led to a separation of philosophy and theology. Three examples are discussed, taken from commentaries on the Sentences. As these examples show, according to a number of ‘moderni’ and ‘nominales’ (Durandus de St Pourçain,William of Ockham, AdamWodeham, Robert Holkot, Marsilius of Inghen), logic and natural reason are not able to exclude all ambiguities and heresies from theological discourse. Thus logic loses its privileged function in theology as arbiter of true reasoning, clearing the way for the rules of traditional and ordinary speech, the ‘vulgus modus loquendi’. Only when logic and reason deal with the natural aspects of creation, do they remain authoritative. When applied to the divine, however, they may easily lead to heresy and error.\n4207 \n4207